Pengaruh Strategi Pembelajaran Active Knowledge Sharing Terhadap Keaktifan Belajar Siswa Kelas X SMK Negeri 1 Angkola Timur - Dedi Azhari STM; Sri Utami Kholilla Mora Siregar; Kasmawati (JURNAL PENDIDIKAN ILMU PENGETAHUAN ALAM, 2024)
The background of the problem in class The aim of this research is to determine the effect of active knowledge sharing learning strategies on student learning activeness and student learning responses to rectilinear movement material at SMK NEGERI 1 ANGKOLA TIMUR. This research is descriptive research involving class (XB) and class (XA). Data was collected through observation sheets. Observation data were analyzed using the learning activity percentage formula. The results of the observation sheet analysis show that after being given the active knowledge sharing learning strategy, the resulting scores were, class (XA) got 85.31% with the "Very Active" criteria and class (XB) got 69.98% with the "Active" criteria and The results of response analysis from the entire questionnaire data obtained were 93.28% gave positive responses and 6.68% chose negative responses with the criteria "Very Interested". So it can be concluded that the use of active knowledge sharing learning strategies has an influence on students' active learning.